Closing the gender gap for a food-secure future - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Why do we need to close the gender gap in food and farming under climate change, and how can we do it? Inspiring women share their views! Featuring: - Mary Robinson, President, Mary Robinson Foundation - Climate Justice - Ann Tutwiler, Director General, Bioversity International - Jane Madgwick, CEO, Wetlands International - Evelyn Namubiru-Mwaura, Policy Officer, Alliance for a Green Revolution in Africa (AGRA) - Surabhi Mittal, International Maize and Wheat Improvement Centre (CIMMYT) - Mariola Acosta, Young Professionals for Agricultural Development (YPARD) Filmed at the seminar Closing the gender gap in farming under climate change. 19 March 2015, Paris. https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action